Sensitivity analysis of the seismic performance of existing masonry buildings - Mendes, N. (2014)
This paper presents a sensitivity analysis taking into account possible variations on the features of masonry buildings. The main objective of the analysis is to compare the seismic performance of a typology of buildings in Lisbon as a function of the changes of its properties with respect to a reference model calibrated from experimental tests. The sensitivity analysis was carried out using non-linear dynamic analysis with time integration and using pushover analysis with distribution of forces proportional to the inertial forces of the structure. The deviations on the seismic response were mainly analysed in terms of maximum load capacity and collapse mechanisms. The results show that the Young’s modulus of the masonry walls, the Young’s modulus of the timber floors and the compressive non-linear properties are the parameters that most influence the seismic performance of this type of tall and weak existing masonry structures. Furthermore, it is concluded that the stiffness of the timber floors significantly influence the strength capacity of the building and the type of collapse mechanism.